Ubenimex combined with Albendazole for the treatment of Echinococcus multilocularis-induced alveolar echinococcosis in mice - Zhou, Zhen; Huayu, Meiduo; Mu, Yalin; Tang, Feng; Ge, Ri-Li (Frontiers in Veterinary Science, 2024)
Alveolar echinococcosis (AE) is a parasitic disease caused by E. multilocularis metacestodes and it is highly prevalent in the northern hemisphere. We have previously found that vaccination with E. multilocularis-Leucine aminopeptidase (EM-LAP) could inhibit the growth and invasion of E. multilocularis in host liver, and Ubenimex, a broad-spectrum inhibitor of LAP, could also inhibit E. multilocularis invasion but had a limited effect on the growth and development of E. multilocularis. In this study, the therapeutic effect of Ubenimex combined with Albendazole on AE was evaluated. Mice were intraperitoneally injected with protoscoleces and imaging examination was performed at week 8 and week 16 to detect cyst change. During this period, mice were intraperitoneally injected with Ubenimex and intragastrically administered with Albendazole suspension. At last, the therapeutic effect was evaluated by morphological and pathological examination and liver function. The results revealed that the combined treatment could inhibit the growth and infiltration of cysts in BALB/c mice infected with E. multilocularis protoscoleces. The weight, number, invasion and fibrosis of cysts were reduced in mice treated with Ubenimex in combination with Albendazole. The same effect was achieved by the single Ubenimex treatment because of its inhibitory effect on LAP activity, but it was less effective in inhibiting the growth of cysts. The levels of ALT, AST, TBIL, DBIL, ALP, and γ-GT were reduced after the combined treatment, indicating that treatment with both Ubenimex and Albendazole could alleviate liver damage. This study suggests that the combined treatment with Ubenimex and Albendazole could be a potential therapeutic strategy for E. multilocularis infections.